2017
DOI: 10.1080/03014460.2017.1328072
|View full text |Cite
|
Sign up to set email alerts
|

Relation of socioeconomic status to overweight and obesity: a large population-based study of Chinese adults

Abstract: SES was associated with general and abdominal overweight/obesity and sex may play a role in such an association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 23 publications
4
35
1
Order By: Relevance
“…This suggests that Brazil's more developed regions in 1996/97 may have been at a more advanced stage of the epidemiological transition than India's most developed states currently. Other studies using measures of household income and educational attainment as the primary exposures and focusing on women in China's most economically prosperous regions have also found a negative association between SEP and prevalence of overweight [29,30]. We also identified a particularly notable convergence in the prevalence of overweight by SEP among women when compared to men.…”
Section: Statement Of Findingssupporting
confidence: 61%
See 1 more Smart Citation
“…This suggests that Brazil's more developed regions in 1996/97 may have been at a more advanced stage of the epidemiological transition than India's most developed states currently. Other studies using measures of household income and educational attainment as the primary exposures and focusing on women in China's most economically prosperous regions have also found a negative association between SEP and prevalence of overweight [29,30]. We also identified a particularly notable convergence in the prevalence of overweight by SEP among women when compared to men.…”
Section: Statement Of Findingssupporting
confidence: 61%
“…One study in China found high-income men and women with low education to be at highest risk of obesity in an economically prosperous province [29]. Another study in China found that higher education was associated with lower odds of overweight among women and higher odds of overweight among men [30]. In South Korea, a country that experienced a remarkable pace of economic growth in previous decades [31], one study still found a positive association of income with obesity among men, whereas they found a negative association among women [32].…”
Section: Statement Of Findingsmentioning
confidence: 99%
“…Socioeconomic status (SES) is reported to have a significant influence on the risk of cardiovascular diseases in adults [8][9][10][11]. SES affects the incidence of cardiovascular diseases through its effect on health status [8].…”
Section: Introductionmentioning
confidence: 99%
“…SES affects the incidence of cardiovascular diseases through its effect on health status [8]. However, its effect on CVD-related health status varies by gender, and different aspects of SES have varying degrees of impact on health status between men and women [9,11]. These different aspects of SES affect the incidence of cardiovascular diseases in a complex manner.…”
Section: Introductionmentioning
confidence: 99%
“…According to the Chinese Residents Nutrition and Chronic Disease Status Report, the obesity rates of Chinese adults aged 18 and above increased from 4.8% in 2002 to 11.9% in 2015 [2]. In addition to genetic predisposition, this obesity epidemic problem is mostly attributed to behavioral risks, including higher calorie intake, shift toward a sedentary lifestyle, and sex may play a role in such an association [3]. However, other determinants, like smoking, may seriously influence individual results in terms of obesity [4].…”
Section: Introductionmentioning
confidence: 99%